THE EFFECT OF SPACING PLANT ON GROWTH AND RESULTS OF SOME SUPERIOR RICE VARIETIES WITH SRI METHOD - Maulidi, Soniari Nurjani (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the effect of plants spacing and waiting for rice varieties on the growth and yield of rice plants using the SRI method and their interactions. The study was carried out in Kalimas Village, Sungai Kakap Subdistrict, Kubu Raya District, on tidal land. This study was conducted the month of May 2018 to August 2018, using a divided plot design consisting of plant spacing of 20 cm x 20 cm, 30 cm x 30 cm, and 40 cm x 40 cm as sub plots and superior rice varieties Situbagendit and Inpari 32 as a main plot. Each treatment was repeated 4 times, with 5 sample plants per map. The observation variables in this study were plant height, maximum number of tillers, number of productive tillers, panicle length, number of grains per panicle, percentage of filled grains per panicle, weight of 1000 grains of grain, weight of grain per clump and weight of grain per plot. The results showed that the treatment of spacing significantly affected the variable number of productive tillers and weight of grain per clump. The results of the analysis of the diversity of superior rice varieties had a significant effect on panicle length and the percentage of grain content and the interaction of the two treatments had no significant effect. Effective spacing is found at a spacing of 40 cm x 40 cm, and the best superior rice varieties are found in the Situbagendit variety. Keywords: Inpari 32 varieties, plants spacing, rice, Situbagendit varieties, SRI method